IMPLEMENTASI MOTORIK HALUS ANAK MELALUI MODEL ATIK (AMATI, TIRU, KERJAKAN) DALAM PEMBELAJARAN PRAKTIK IBADAH DI KELOMPOK BERMAIN ASA BUNDA - Ana Amrulloh; Ahmadi (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This study aims to analyze the implementation of the ATIK (Observe, Imitate, Do) model in developing children's fine motor skills through worship practice learning at the Asa Bunda Playgroup. The study used a qualitative approach with a case study to gain a deeper understanding of the learning process and dynamics of children's fine motor development. Data collection techniques included observation, interviews, and documentation, followed by interactive analysis through data reduction, data presentation, and conclusion drawing. The results indicate that the ATIK model is effective in developing children's fine motor skills through systematic stages. The observe stage plays a role in building visual understanding and movement planning, the imitate stage activates sensorimotor coordination through imitation, and the do stage strengthens skills through repeated independent practice. Implementation of this model not only improves the accuracy and coordination of hand movements but also encourages independence, self-confidence, and active involvement in learning. Furthermore, worship practice as a learning context provides added value through the simultaneous integration of motor, cognitive, and spiritual aspects, resulting in a holistic and meaningful learning experience. Thus, the ATIK model can be an effective alternative pedagogical approach in early childhood education based on Islamic values.